2002
DOI: 10.1038/sj.bjp.0704447
|View full text |Cite
|
Sign up to set email alerts
|

Pathological role of a constitutively active population of α1D‐adrenoceptors in arteries of spontaneously hypertensive rats

Abstract: 1 The role of a constitutively active population of a 1D -adrenoceptors was analysed in arteries obtained from spontaneously hypertensive rats (SHR) and controls (WKY) divided into three groups: young prehypertensive, adult hypertensive, and adult animals chronically treated with captopril (50 mg kg 71 per day orally) in order to prevent the hypertensive state. 2 In adult SHR, a signi®cant increase in BMY 7378 potency (not in prazosin potency) was observed in aorta, mesenteric artery, and the ®rst and second b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 20 publications
5
33
0
Order By: Relevance
“…As shown in Table 3 and Fig. 6, a significant increase in the potency (pIC 50 ) of the selective ␣ 1D antagonist BMY 7378 was seen in aortas from adult SHRs versus WKY animals confirming the major functional role of the ␣ 1D -ARs previously reported in aorta from adult hypertensive rats but not in young animals (previous results, Gisbert et al, 2002). However, no such change was found with the selective ␣ 1A antagonist 5-methylurapidil (Table 3; Fig.…”
Section: Downloaded Fromsupporting
confidence: 49%
See 1 more Smart Citation
“…As shown in Table 3 and Fig. 6, a significant increase in the potency (pIC 50 ) of the selective ␣ 1D antagonist BMY 7378 was seen in aortas from adult SHRs versus WKY animals confirming the major functional role of the ␣ 1D -ARs previously reported in aorta from adult hypertensive rats but not in young animals (previous results, Gisbert et al, 2002). However, no such change was found with the selective ␣ 1A antagonist 5-methylurapidil (Table 3; Fig.…”
Section: Downloaded Fromsupporting
confidence: 49%
“…An increased functional role of ␣ 1D -ARs has been proposed as one of the changes involved in the hypertensive increase of vascular resistance (VillalobosMolina et al, 1999;Gisbert et al, 2002;Tanoue et al, 2002a,b;Ziani et al, 2002;D'Ocon, 2003;Lyssand et al, 2008), but the mechanism responsible for this increase has not been elucidated previously.…”
mentioning
confidence: 99%
“…In the MRA of LNHR, no significant changes in either the CRCs of phenylephrine or the expression of α 1 -ARs were found, as reported in SHR [34] and as the present results show. Thus the α 1 -adrenergic response in MRA is not influenced by hypertension or chronic L -NAME treatment.…”
Section: Discussionsupporting
confidence: 79%
“…As previously reported [12], the greater potency of phenylephrine observed in the aortas of SHR can determine the pathological increase in tone linked to the genesis of the hypertensive state. This increased sensitivity correlates not only with a significant increase in the expression of the three α 1 -AR subtypes in the aorta [12] but also with an increase in α 1D -AR functionality, which is the main subtype in this vessel [15,34,35,36,37], with a major affinity for agonists [15,38]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found differences in blood vessels when comparing SHR and WKY (Cox, 1979;Gisbert et al, 2002;Leal et al, 2008;Lee, 1987); Rocha-Pereira et al, 2009). Findings from the study by Gisbert and co-workers (2002), showed that the population of constitutively active α 1D -adrenoceptors is significantly increased in aorta and mesenteric www.intechopen.com artery from adult SHR when compared to WKY -these results verify that the vessels in question, from hypertensive animals, have an increased population of constitutively active receptors as well as an increased functionality of the α 1D -subtype, with respect to normotensive animals.…”
Section: Adenosinergic System and Hypertensionmentioning
confidence: 99%